2020
DOI: 10.3168/jds.2020-18514
|View full text |Cite
|
Sign up to set email alerts
|

Whole-flint corn grain or tropical grass hay free choice in the diet of dairy calves

Abstract: Tropical grass hay feeding is related to improved ruminal health; however, it may decrease energy intake. On the other hand, whole-flint corn grain may be an alternative fiber source in the diet of dairy calves. Forty-two Holstein calves were used in a randomized block design, considering sex, birth date, and weight at 21 d of age, when the supply of whole-flint corn grain or tropical grass hay started. Three component-fed solid diets were compared: (1) starter concentrate only during the preweaning and starte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 55 publications
0
3
1
4
Order By: Relevance
“…The solid diets intake increases microbial populations' development, resulting in higher production of SCFA (Baldwin et al ., 2004). Depending on the type and quality of the diet fed to the calves, the GIT's morphophysiology may be altered (Li et al ., 2011; Toledo et al ., 2020). In addition, the provision of drinking water is essential to maintain ruminal activity.…”
Section: Microbiota and Ruminal Development In Dairy Calvesmentioning
confidence: 99%
See 1 more Smart Citation
“…The solid diets intake increases microbial populations' development, resulting in higher production of SCFA (Baldwin et al ., 2004). Depending on the type and quality of the diet fed to the calves, the GIT's morphophysiology may be altered (Li et al ., 2011; Toledo et al ., 2020). In addition, the provision of drinking water is essential to maintain ruminal activity.…”
Section: Microbiota and Ruminal Development In Dairy Calvesmentioning
confidence: 99%
“…Many recent studies have demonstrated that access to chopped hay promotes starter concentrate intake in calves, contrary to traditional recommendations (Jiao et al ., 2016; Toledo et al ., 2020). Castells et al .…”
Section: Microbiota and Ruminal Development In Dairy Calvesmentioning
confidence: 99%
“…Equivalente ao observado em experimentos conduzidos pela nossa equipe (Poczynek et al, 2019;De Paula et al, 2017), houve a ocorrência de diarreia na segunda e terceira semanas de vida, porém sem a redução do ganho de peso. Diferente do relatado por Toledo et al (2020), que observaram que animais alimentados com maior teor de carboidratos não fibrosos, em função do fornecimento de milho grãos à vontade, apresentavam fezes mais fluídas em comparação com dietas contendo feno, devido ao escape do milho no rúmen chegando ao intestino grosso causando uma acidose cecal. No presente estudo, o fornecimento de concentrado contendo silagem de milho grão reconstituído, ou seja, com milho mais fermentável, não causou o mesmo resultado, provavelmente pelo melhor aproveitamento desse ingrediente no rúmen e pouco escape para o intestino grosso.…”
Section: Discussionunclassified
“…Em trabalho de Oltramari et al (2016), substituindo o milho por polpa cítrica, observou-se que essa substituição não afetou o consumo de concentrado, assim como o consumo, o peso vivo e ganho de peso médio diário. Já em outro trabalho, realizado por Poczynek et al (2020), substituindo parte do milho por casca de soja e analisando diferentes teores de FDN na dieta sólida de bezerros leiteiros, observou-se que a dieta com maior teor de FDN (31%) não alterou o consumo de concentrado dos animais. Neste mesmo trabalho, não houve influência das dietas em relação ganho de peso, eficiência alimentar e peso vivo.…”
Section: Composição De Dieta Sólida Para Bezerrosunclassified
“…O rúmen-retículo teve seu volume mensurado através de enchimento por água após seu esvaziamento, e a quantidade de água que encheu por completo o rúmen-retículo foi pesada, seguindo a metodologia descrita por (Toledo et al, 2020), portanto a densidade da água foi considerada igual ao seu peso (kg=litro). Em seguida os componentes do trato gastrointestinal (rúmen, retículo, omaso, abomaso, ceco, intestino grosso e intestino delgado)…”
Section: Abate Dos Animais E Características Da Carcaçaunclassified